PENGARUH KEPEMILIKAN INSTITUSIONAL DAN DEWAN KOMISARIS INDEPENDEN TERHADAP TAX AVOIDANCE PADA PERUSAHAAN LQ-45 YANG TERDAFTAR DI BEI PERIODE 2015-2017 - Nensi Yuniarti; Elvis Nopriyanti Sherly; Dewi Nopita Sari (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2020)
Â This study aims to examine (1) Institutional ownership Against Tax Avoidance and (2) Independent Board of Commissioners Against Tax Avoidance in LQ-45 companies registered in Indonesia Stock Exchange (IDX). This research is quantitative research. The population in this study were all LQ-45 companies listed on the Stock Exchange in 2015-2017. While the sample of this study was determined by purposive sampling method to obtain 29 sample companies. The type of data used is secondary data obtained from www.idx.co.id and sample company websites. The analytical method used is multiple linear regression analysis. Based on the results of multiple linear regression analysis with a significance level of 5%, the results of the study concluded: institutional ownership and independent board of commissioners proved to have a significant effect on tax avoidance. The results of this study, it is suggested to add other variables that are thought to influence tax avoidance such as: audit quality, audit committee, management compensation, and managerial ownership.